Interactions between extracorporeal support and the cardiopulmonary system - Bachmann, Kaspar F.; Berger, David; Moller, Per Werner (Frontiers in Physiology, 2023)
This review describes the intricate physiological interactions involved in the application of extracorporeal therapy, with specific focus on cardiopulmonary relationships. Extracorporeal therapy significantly influences cardiovascular and pulmonary physiology, highlighting the necessity for clinicians to understand these interactions for improved patient care. Venoarterial extracorporeal membrane oxygenation (VA ECMO) unloads the right ventricle (RV) and increases left ventricular (LV) afterload, potentially exacerbating LV failure and pulmonary edema. Veno-venous (VV) ECMO presents different challenges, where optimal device and ventilator settings remain unknown. Influences on right heart function and native gas exchange as well as end-expiratory lung volumes are important concepts that should be incorporated into daily practice. Future studies should not be limited to large clinical trials focused on mortality but rather address physiological questions to advance the understanding of extracorporeal therapies. This includes exploring optimal device and ventilator settings in VV ECMO, standardizing cardiopulmonary function monitoring strategies, and developing better strategies for device management throughout their use. In this regard, small human or animal studies and computational physiological modeling may contribute valuable insights into optimizing the management of extracorporeal therapies.